ANALISIS EFISIENSI, EFEKTIVITAS, KONTRIBUSI, PERTUMBUHAN PENERIMAAN REALISASI, DAN PERTUMBUHAN WAJIB PAJAK BUMI DAN BANGUNAN PERKOTAAN TERHADAP PENDAPATAN ASLI DAERAH KOTA PALEMBANG - M. Thoyib; Bainil Yulina; M. Reynaldi Dwi Saputra; Riza Wahyudi; Darul Amri (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2021)
This study was conducted to determine the factors that influence the receipt of the Rural and Urban Land and Building Tax (PBB-P2) on Regional Original Income in Palembang City. The factors studied are efficiency, effectiveness, contribution, growth of realized revenue, and growth of taxpayers partially and simultaneously. The sampling used in this study is the Saturated Sampling Technique method using secondary data from the Regional Government Financial Reports (LKPD) audited by the BPK and Land and Building Tax Realization Reports which are analyzed using multiple regression analysis with the help of Statistical Product Software for the Service Solution (SPSS) version 26 for windows. As a result, it is estimated that there is an effect of the independent variable on the dependent both partially and simultaneously. The coefficient with the highest effect on PAD is efficiency of 0.932 and the coefficient with the lowest effect is the revenue growth rate of 0.219. As much as 72.1% can be explained by independent variables and the remaining 27.9% is influenced by other factors not explained in this study.